An Assessment on Knowledge of National Health Insurance Program of Nepal among Teaching Faculty of Tribhuvan University - Thuma Kumari Paudel; Govinda Prasad Adhikari; Parbati Kumari Upadhyay (Journal of Population and Development, 2026)
The national health insurance program helps to ensure affordable access to quality healthcare for the people. Due to a lack of adequate understanding of health insurance, many people have not used the health insurance service in Nepal. This paper aims to examine the knowledge of the national health insurance program among faculty members. This is a cross-sectional research among the faculty members of Tribhuvan University of Nepal. The selection of the campus as a purposive sampling method, and sampled (52) using a random sampling (lottery) method. The researcher has used a self-administered structured questionnaire to collect the required data. Data were entered through SPSS 20th version software and utilized a descriptive analysis to present the data. The paper has found that 81 percent of university faculty have knowledge of NHIP. Among them, female respondents have higher (82 percent) knowledge than males (80 percent). The knowledge of the national health insurance program varied by age, educational level, designation, and family size. Radio, TV, and newspapers are major (67 percent) sources of knowledge, more than social media. About 48 percent of respondents know the process of enrollment, 54 percent know the maturation time, 65 percent know the renewal period of the program, and only 27 percent of respondents know the amount that a normal family with five members should pay for enrollment in NHIP. However, this article provides baseline information, but a national level survey is recommended to find the real status.